Chemical composition, antioxidant activities, and enzyme inhibitory effects of Lespedeza bicolour Turcz. essential oil - Jiadong Zhu; Ziyue Xu; Xu Liu (Journal of Enzyme Inhibition and Medicinal Chemistry)
Lespedeza bicolour Turcz. is a traditional medicinal plant with a wide range of ethnomedicinal values. The main components of L. bicolour essential oil (EO) were β-pinene (15.41%), β-phellandrene (12.43%), and caryophyllene (7.79%). The EO of L. bicolour showed antioxidant activity against ABTS radical and DPPH radical with an IC50 value of 0.69 ± 0.03 mg/mL and 10.44 ± 2.09 mg/mL, respectively. The FRAP antioxidant value was 81.96 ± 6.17 μmol/g. The EO had activities against acetylcholinesterase, α-glucosidase, and β-lactamase with IC50 values of 309.30 ± 11.16 μg/mL, 360.47 ± 35.67 μg/mL, and 27.54 ± 1.21 μg/mL, respectively. Molecular docking showed methyl dehydroabietate docked well with all tested enzymes. Sclareol and (+)-borneol acetate showed the strongest binding affinity to α-glucosidase and β-lactamase, respectively. The present study provides a direction for searching enzyme inhibitors for three tested enzymes and shows L. bicolour EO possesses the potential to treat a series of diseases.